Bioinspired artificial nanovesicles engineered from 3D spheroid-cultured UC-MSCs enhance angiogenic activity in vitro: functional proof-of-concept for ischemic applications - Gangadaran, Prakash; Rajendran, Ramya Lakshmi; Oh, Ji Min; Son, Jaeyoung; Hong, Chae Moon; Ahn, Byeong-Cheol (Frontiers in Cell and Developmental Biology, 2026)
Artificial nanovesicles (aNVs) derived from cells may mimic naturally secreted extracellular vesicles (EVs) and are becoming popular in biomedical research. We isolated aNVs from two-dimensional (2D)- and three-dimensional (3D)-cultured umbilical cord-derived mesenchymal stem cells (UC-MSCs) (aNVs2D and aNVs3D, respectively) and characterized them using Western blotting and electron microscopy. The aNVs3D showed higher expression of IL-6 and SDF-1α than aNVs2D. In vitro treatment with aNVs2D and aNVs3D resulted in their internalization into endothelial cells and the subsequent alteration of endothelial cell proliferation, migration, and tube formation. Both aNVs were positive for EVs and cell markers and were round in shape. Furthermore, aNVs3D treatment enhanced endothelial cell proliferation, migration, and tube formation more effectively than aNVs2D treatment. Our study demonstrates that aNVs3D are potent inducers of angiogenesis, indicating their potential in cell-free ischemia treatment.